PROGRESS IN THERMO-ABRASIVE BLASTING SYSTEMS - Gorlach, I.A. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Quality of surface preparation of components and structures for further painting and/or coating is important in many fields of engineering. One of the most widely used methods of surface preparation is abrasive blasting. In the last few years, a new method for surface preparation has evolved, namely thermo-abrasive blasting. This technique utilises a high enthalpy thermal jet, generated by the thermo-abrasive blasting gun, to propel abrasive particles. Thermo-abrasive blasting has a number of advantages over conventional abrasive blasting, which were assessed during trials. This paper describes a progress in the applications of thermo-abrasive blasting as well as future potentials for South African industry. The performance data and economic comparison of conventional and thermo-abrasive blasting are also presented in this paper. AFRIKAANSE OPSOMMING: Die gehalte van voorbereiding van komponent- en struktuuroppervlaktes is oral belangrik in ingenieurswesetoepassings. Wat vrywel tot die hede dikwels gebruik was, is straalskuring. Onlangs het 'n nuwe metode tot stand gekom naamlik termostraalskuring. Die metode maak gebruik van 'n ho